4 Laws of New Hampshire, Revolutionary Period 273 (Henry Harrison Metcalf ed., 1916) - (:unkn) unknown (My University, 1780)
An Act for Forming & Regulating The Militia within this State, and for Repealing All the Laws heretofore made for that Purpose: Militiamen had to attend musters and drills, and sometimes had to march off to fight in distant locations. Further, all males under 70 who were capable of bearing arms were put on the "alarm list." This meant that they had to have all the same arms and gear as militiamen
Keywords: MILITIAS; REQUIRED POSSESSION